2013
DOI: 10.24126/jobrc.2013.7.1.245
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation of Gerbera (Gerbera jamesonii Bolus)

Abstract: Gerbera plant Gerbera jamesonii is classified according to the flower colors to four strains: white, yellow, pink and purple. Capitulum and scape explants were tested on MS medium in half or full salts strength, supplemented with different combinations of plant growth regulators cytokinins kintin (Kin) and benzel adinine (BA), auxin indolacitic acid (IAA). Results revealed that the capitulum showed better response to shoot formation 64.13% whereas the scape did not show response. Yellow flowers showed higher r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…Cytokinin to auxin ratio is critical. It is clear from the above findings that cytokinin (BAP) is a potent plant growth regulator for generation of Shailaja (2002) who obtained highest multiplication rate in gerbera with 3.0mgL -1 BAP. Results presented in Table 2 show that average length of shoots decreased significantly with higher concentration of cytokinin (BAP) when in combination with NAA.…”
Section: Resultsmentioning
confidence: 92%
“…Cytokinin to auxin ratio is critical. It is clear from the above findings that cytokinin (BAP) is a potent plant growth regulator for generation of Shailaja (2002) who obtained highest multiplication rate in gerbera with 3.0mgL -1 BAP. Results presented in Table 2 show that average length of shoots decreased significantly with higher concentration of cytokinin (BAP) when in combination with NAA.…”
Section: Resultsmentioning
confidence: 92%
“…The best initiation and proliferation of shoots were observed on MS medium with 1 mg/L BAP, 0.030 mg/L IBA, and 0.025 mg/L NAA, which showed almost identical results. In another study, [11] found that the capitulum responded better to shoot formation at 64.13%. In contrast, there was no response observed on the scale.…”
Section: Introductionmentioning
confidence: 90%